Some Properties of Certain Integral Operators on New Subclasses of Analytic Functions with Complex Order - Aabed Mohammed; Maslina Darus (Journal of Applied Mathematics)
We define new subclasses of p-valent meromorphic functions with complex order. We prove some properties for certain integral operators on these subclasses.